Analisis Gaya Potong pada Pemesinan Bubut Magnesium AZ31 Dalam Keadaan Kering - Ibrahim, Gusri Akhyar; Gustiyawan, Ahmad; Yahya, Ahmad; Hamni, Arinal; Burhanuddin, Yanuar (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2023)
The cutting of magnesium alloy by using a single cutting method as known by turning process. In the machining process, the cutting tool used in long time will experience wear and damage. The tool wear on the cutting edge was caused by cutting force that took place during cutting process. The cutting force depend one tool geometry, workpiece material, tool material and cutting condition. The objective of this research is to analyze the cutting force during turning process using the cutting force measurement. In this experiment, the cutting tool used of High Speed Steel, workpiece material of magnesium alloy and strain gauge sensor to measure cutting force. The results show that the spindle speed and cutting speed influenced on cutting force, in which increasing in spindle speed and cutting speed produced low cutting force. Whereas, increasing in feed rate and depth of cut significant effect on increasing the cutting.force